Expanding access to viral load testing in Nigeria; the impact of third party logistics - Adeiye, Ajani Love; Faith, Ajani Olumide; Felix, Sanni Olaniyi; Paul, Abiodun Olaiya; Nwofe, Justin Onyebuchi; Rukema, Kaniki Freddy; Mallak, Shadi Kafi (International Journal Of Community Medicine And Public Health, 2019)
Background: Access to viral load testing in Nigeria remains a key challenge in achieving the Joint United Nations Program on HIV/AIDS (UNAIDS) 90:90:90 targets in the fight against HIV/AIDS. This study investigates the impact of 3 party logistics (3PL) on expanding access to viral load testing. Methods: This exploratory, case study research was carried out in Abuja in December, 2018, using in-depth interview method. Open-ended questions were used to interview nine staff from the three polymerase chain reaction laboratories in Federal Capital Territory. The audios of interviews were recorded and transcribed on paper. The data was analyzed using SPSS version 24. Results: This study revealed that the adoption of 3PL services has helped to overcome major challenges of viral load testing such as late delivery of samples, late collection of results, and rejection problems; thereby reduced sample rejection frequencies, increased efficiency, reduced turnaround time and ease viral load testing processes. Though the adoption of 3PL has helped to overcome major challenges of viral load testing, however, the challenges still facing viral load testing include the 3PLs bringing samples at any time-even at closing hours, not delivering results to facilities on time after pickup, poor medical backgrounds and inability of 3PLs to enforce instructions on facilities. However, respondents expressed satisfaction with the services of the 3PLs. Conclusions: The findings of this study revealed that the adoption of 3PL service into viral load transport logistics has positive impacts on the process. However, only one of the laboratories uses two 3PL providers while other two use only one.